Yb:CALYO-based femtosecond chirped pulse regenerative amplifier for temporally resolved pump-probe spectroscopy - A. S. Rudenkov; V. E. Kisel; A. S. Yasukevich; K. L. Hovhannesyan; A. G. Petrosyan; N. V. Kuleshov (Приборы и методы измерений)
Diode-pumped femtosecond chirped pulse regenerative amplifiers based on Yb3+-materials are of practical importance for wide range of scientific, industrial and biomedical applications. The aim of this work was to study the amplification of broadband chirped femtosecond pulses in regenerative amplifier based on Yb3+:CaYAlO4 crystal.Such systems use femtosecond mode-locked lasers as seed pulse sources and amplify nJ-seed pulses to sub-mJ energy range. Most chirped pulse regenerative amplifier systems described in the literature use seed lasers with typical pulse spectral width at the level of 10–15 nm full width at half maximum (FWHM) that limit the seed pulse duration of about 90 fs and amplified pulse duration at the level of 200 fs due to strong influence of gain narrowing effect on the amplified pulse parameters. Yb3+-doped crystals with wide and smooth gain bandwidth as an active medium of chirped femtosecond pulse regenerative amplification systems allow to reduce negative contribution of gain narrowing effect and lead to shortening of amplified pulses. In this research we study the chirped pulse regenerative amplification of broad-band femtosecond pulses (60 nm spectral width FWHM) in the Yb3+:CaYAlO -based chirped pulse regenerative amplifier. Substantial reduction of the amplified pulse duration down to 120 fs (19.4 nm spectral width FWHM) with average power of 3 W at 200 kHz pulse repetition frequency was demonstrated without any gain narrowing compensation technique.The results of experimental investigation of broad-band seeded Yb3+:CaYAlO -based chirped pulse regenerative amplifier are reported for the first time to our knowledge. 120 fs-pulses (19.4 nm FWHM) with average output power of 3 W were demonstrated without any gain narrowing compensation technique. Despite the significant reduction of amplified pulse duration the task of improvement group velocity dispersion balance (including high orders of group velocity dispersion) remains relevant.